(untitled) (American Journal of Pedagogical and Educational Research, 2023)
When I went to Bobotog in Surkhandarya region, I was surprised by the fact that pistachio trees have decreased a lot these days, that their price is high in the market, and that the indigenous people of Bobotog value pistachios very much. All this made me want to know more about this tree. Currently, pistachios are found only in the Bobotog regions of Samarkand region and Surkhandarya region. Bobotog forestry is famous for its pistachios. Of the farm’s 77,000 ha area, 27,000 ha are occupied by pistachio trees. Bobotog almonds are smaller and differ from pistachios grown in other countries by their taste and richness in nutrients. Since "foreign" pistachios are more moist and saturated with a large dose of sunlight, pistachios grown in Uzbekistan are dry and caloric. In fact, pistachios are a priceless gift of nature.